The Values and Limitations of FDG-PET/CT for Diagnosis of Hibernoma - Jong Hoon Park; Koichi Ogura; Tomohiro Fujiwara; Akihito Nagano; Kunihiko Numoto; Takashi Terauchi; Akihiko Yoshida; Akira Kawai (Case Reports in Orthopedics)
Hibernoma is a rare benign lipogenic tumor of brown fat that develops in a wide variety of locations. Although the features of hibernoma demonstrated by MRI resemble those of liposarcoma, recent FDG-PET/CT studies have documented higher radiotracer uptake than liposarcoma, suggesting that FDG/PET/CT is useful for differentiating hibernoma from liposarcoma. Here we report two cases of hibernoma that showed relatively lower SUVs than those reported previously, lying within the range for liposarcoma. Our findings emphasize that hibernoma needs to be included in the differential diagnosis of any fat-containing tumor showing intense accumulation by FDG-PET/CT. Although it is unlikely that such a rare condition could be reasonably diagnosed on the basis of MRI and FDG-PET/CT alone due to possible SUV overlap between hibernoma and liposarcoma, it is important to recognize this extremely rare lipogenic tumor for accurate diagnosis and appropriate management.